Analysis of Determination of Sanctions Against Narcotics Abusers Who Experience Mental Disorders (Study of Denpasar District Court Decisions) - Mohammad syahrir DJ.Pano; Fenty U. Puluhulawa; Avelia Rahmah Y. Mantali (Universitas Negeri Gorontalo, 2023)
Research findings show that the proportion of drug users who suffer from mental disorders is still very high compared to that of drug users who do not suffer from mental disorders. The reason is that the use of drugs can cause addiction, which means that users will continue to do so that which affects the central nervous system and results in mental disorders in drug users, for example in two cases in the Denpasar District Court with cases of narcotics abuse where the defendant had bipolar disorder. This study concludes that the judge's consideration includes the reasons for bipolar mental disorder as mitigating factors. In the case of abuse of narcotics, the Defendants BJJ and YAR, even though they were bipolar, still did not abolish the sentence against the two Defendants in these two different cases..